PROOXIDANT-ANTIOXIDANT HOMEOSTASIS OF RATS’ SKELETAL MUSCLE IN CONDITIONS OF HYPO - AND HIPERMELATONONEMIA IN AGING - Гільмутдінова, М.Ш. (World of Medicine and Biology, 2014)
The results of investigation of influence of conditions and the lack of excess melatonin skeletal muscle (on the example of the quadriceps muscle of thigh rats) and prooxidant-antioxidant system in aging are presented in the article.